Functional Outcomes of an Interdisciplinary Outpatient Rehabilitation Program for Patients with Malignant Brain Tumors. Issue 9 (14th March 2018) - Shahpar, Samman; Wong, Alex W.K.; Keeshin, Susan; Eickmeyer, Sarah M.; Semik, Patrick; Kocherginsky, Masha; McCarty, Stacy
Abstract: Background: Malignant brain tumors cause significant impairments in function because of the nature of the disease. Nevertheless, patients with malignant brain tumors can make functional gains equivalent to those with stroke and traumatic brain injury in the inpatient rehabilitation setting. However, the efficacy of outpatient rehabilitation in this population has received little study. Objective: To determine if an interdisciplinary outpatient rehabilitation program will improve functional outcomes in patients with malignant brain tumors. Design: Nonrandomized prospective longitudinal study. Setting: Six affiliated outpatient sites of one institution. Patients: Forty‐nine adults with malignant brain tumors were enrolled. Methods: Patients received interdisciplinary therapy services, with duration determined by the therapist evaluations. The therapists scored the Day Rehabilitation Outcome Scale (DayROS) and Disability Rating Scale (DRS) on admission and discharge. The caregivers filled out the DRS at discharge, 1 month, and 3 months after discharge. Main Outcome Measurements: The primary study outcome measure was the DayROS, which is a functional measure similar to the Functional Independence Measure. DRS was another functional outcome measure assessing basic self‐care, dependence on others, and psychosocial adaptability. Results: Forty‐six of 49 enrolled patients (94%) completed the day rehabilitation program. The average length of stay was 76.9 days. There was a significant improvement in total DayROS ( P < .001), mobility ( P < .001), Activities of Daily Living ( P < .001), and communication ( P < .001) DayROS subscores from admission to discharge. There were no significant changes over time in the DRS scores. Women had higher DayROS gains ( P = .003) and better therapist DRS scores from admission to discharge than men ( P = .010). Conclusions: Patients with malignant brain tumors can make functional gains in an interdisciplinary outpatient rehabilitation program. This level of care should be considered in this patient population. Level of Evidence: II